PENGARUH WEIGHT TRAINING DENGAN METODE PYRAMID SET TERHADAP PENURUNAN PERSENTASE LEMAK ATLET ANGKAT BERAT KOTA MALANG - mohamad ahya ulumudin (Media Ilmu Keolahragaan Indonesia, 2025)
Reducing body fat percentage is one of the important goals in a physical training program. The purpose of this study was to investigate the effect of the pyramid set training method on reducing body fat percentage in athletes. The subjects in this study were 10 male weightlifters from Malang City who underwent a pyramid set training program for 20 sessions, with body fat percentage measurements taken before and after the intervention. The results showed a significant decrease in body fat percentage after following the pyramid set training program, indicating the effectiveness of this method in burning fat. Based on the research that has been done, weight training using the pyramid set method has an effect on reducing fat percentage in weightlifters from Malang City.